Depletion of 13C in CO in the Atmosphere of Mars Suggested by ExoMars-TGO/NOMAD Observations - S. Aoki; K. Shiobara; N. Yoshida; L. Trompet; T. Yoshida; N. Terada; H. Nakagawa; G. Liuzzi; A. C. Vandaele; I. R. Thomas; G. L. Villanueva; M. A. Lopez-Valverde; et al. (The Planetary Science Journal, 2023)
The atmosphere of Mars is mainly composed by carbon dioxide (CO _2 ). It has been predicted that photodissociation of CO _2 depletes ^13 C in carbon monoxide (CO). We present the carbon ^13 C/ ^12 C isotopic ratio in CO at 30–50 km altitude from the analysis of the solar occultation measurements taken by the instrument Nadir and Occultation for Mars Discovery on board the ExoMars Trace Gas Orbiter (ExoMars-TGO). We retrieve ^12 C ^16 O, ^13 C ^16 O, and ^12 C ^18 O volume mixing ratios from the spectra taken at 4112–4213 cm ^−1 , where multiple CO isotope lines with similar intensities are available. The intensities of the ^12 C ^16 O lines in this spectral range are particularly sensitive to temperature, thus we derive the atmospheric temperature by retrieving CO _2 density with simultaneously measured spectra at 2966–2990 cm ^−1 . The mean δ ^13 C value obtained from the ^13 C ^16 O/ ^12 C ^16 O ratios is −263‰, and the standard deviation and standard error of the mean are 132‰ and 4‰, respectively. The relatively large standard deviation is due to the strong temperature dependences in the ^12 C ^16 O lines. We also examine the ^13 C ^16 O/ ^12 C ^18 O ratio, whose lines are less sensitive to temperature. The mean δ value obtained with ^12 C ^18 O instead of ^12 C ^16 O is −82‰ with smaller standard deviation, 60‰. These results suggest that CO is depleted in ^13 C when compared to CO _2 in the Martian atmosphere as measured by the Curiosity rover. This depletion of ^13 C in CO is consistent with the CO _2 photolysis-induced fractionation, which might support a CO-based photochemical origin of organics in Martian sediments.